ChemInform Abstract: Halide Effects on Cyclopropenium Cation Promoted Glycosylation with Deoxy Sugars: Highly α‐Selective Glycosylations Using a 3, 3‐Dibromo‐1, 2‐diphenylcyclopropene Promoter. Issue 9 (5th March 2013) - Nogueira, Jason M.; Issa, John Paul; Chu, An‐Hsiang Adam; Sisel, Jordan A.; Schum, Ryan S.; Bennett, Clay S.
Abstract α‐Selective dehydrative glycosylations of 2‐deoxy sugar donors are achieved using a new cyclopropenium cation promoter system.